BIOLOGICAL BASE OF SKIPJACK AS THE FOUNDATION FOR SUSTAINABLE FISHERIES MANAGEMENT IN THE NORTH MALUKU PROVINCE - Amirul Karman; Sulaeman Martasuganda; M. Fedi A. Sondita; Mulyono S. Baskoro (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Skipjacks in the western and southern waters of North Maluku Province were caught using pole and line with FADs. Skipjack usually swims near the surface water and tends to be classified as a juvenile skipjack that caught during fishing activities. The study objective was to analyze biological data of skipjack including length weight relationship, growth, length at first maturity/lm and catch size, size composition and gonad maturity. Skipjack samples were caught in the waters of the western (zone A) and southern (zone b) areas of North Maluku Province, from April 2012 until May 2013. The sudy results show the value bof skipjack caught around FADs at zone A and B were similar as b=3. This indicates that the growth of skipjack in both areas was categorized as in isometric pattern. L∞ of skipjack caught at zone A was 75 cm at the age of 56 months and at zone B was 76 cm at the age of 56 months. Lm value skipjack caught in zone A and zone B was obtained by 43 cm, with a range of long-forked skipjack caught in zone A from 26.0 to 72.0 cm, and at zone B from 26- to 71 cm , The gonad maturity at zone A and B, was obtained in the similar stages as maturity stages I, II, III,IV, and V. TKG V of the skipjack caught around FADs zone A is found in March and B in July, so it can be presumed skipjack in two zones throughout the year with peak spawning occurs in March for zone A and B in July.Keywords: Biological base, skipjack, fishery management, North Maluku